Geographic range, habitats, and host plants of bromeliad-living jumping spiders (Salticidae) - Romero, Gustavo Q. (Blackwell Publishing, 2006)
Although spiders are a very diverse group on vegetation, their associations with plants are poorly known. Some salticid species specifically use Bromeliaceae as host plants in some regions of South America. In this study, I report the geographic range of these spider-bromeliad associations, and whether the spiders inhabit particular bromeliad species and vegetation types, as well as open areas or interior of forests. Nine salticid species were found to be associated with up to 23 bromeliad species in cerrados (savanna-like vegetation), semideciduous and seasonal forests, coastal sand dune vegetation, restingas, inselbergs, highland forests, chacos, and rain forests at 47 localities in Brazil, Paraguay, Bolivia, and Argentina. Some species were typically specialists, inhabiting almost exclusively one bromeliad species over a large geographic range (e.g., Psecas chapoda on Bromelia balansae), whereas others were generalists, occurring on up to 7-8 bromeliad species (e.g., Psecas sp., Eustiromastix nativo, and Coryphasia sp. 1). The regional availability of bromeliad species among habitats may explain this pattern of host plant use. More jumping spiders were found on bromeliads in open areas than on bromeliads in the interior of forests. These results show that several jumping spider species may be strictly associated with the Bromeliaceae in the Neotropics. This is one of the few studies to show host-specific associations for spiders on a particular plant type over a wide geographic range.
Keywords: animal-plant interactions; Bromeliaceae; distribution patterns; Hábitat; host plant; jumping spiders; South America; Specific association